Human resource management and creativity in academic spin-offs: the case of IST Spin-off Community - Luís, Conceição; Sousa, Cristina (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
This paper aims to study the role of Human Resource Management (HRM) in promoting creativity in small technology-based companies, originating in academia, through the case study of companies belonging to the Instituto Superior Técnico (IST) Spin-off Community. More specifically, it is intended to assess the contribution of HRM practices, including recruitment and selection, training and development, rewards and benefits and performance evaluation, in fostering creativity and success of new technology-based companies. Technology-based companies and academic spin-offs are currently in the agendas of researchers and policy makers. It is stressed their role in the knowledge transfer from university to industry and in the creation of highly qualified employment. The success of these companies is strongly linked to their innovation capacity, and thus the creativity management of individuals and teams is of great relevance. In this process HRM practices are of utmost importance. In order to investigate the relation between HRM and creativity in academic spin-offs we draw on three different bodies of knowledge: entrepreneurship, HRM practices and creativity management. Despite the proliferation of studies in each of these areas, the bridges between them are yet to build. For example, the work developed by Amabile et al. (1996), recognizes the importance of the organizational context and of the firm´s management in the creative process, but does not consider explicitly the HRM, neither the specificity of academic spin-offs. For its part, literature on HRM practices is focused on large companies, while spin-offs tend to be young SMEs. Drawing on the extant literature, we build an analytic framework that intends to throw some links between the tree areas above mentioned and thus to contribute to fill the gap found in the literature. The proposed analytical framework includes dimensions related to the organizational behavior (climate, leadership and structure), the HRM practices and the creativity management (creativity components, enhancers and inhibitors according to Amabile (1998)). The framework was applied to the IST Spin-off Community case. Based on a purposefully built semi-structured questionnaire, 18 interviews were carried out. The interviews were conducted in the first quarter of 2012, involving the companies’ founders or CEOs. The results reveal some specificity of these companies in terms of HRM practices, namely in terms of selection, rewards and training and development. They also reveal that some HRM practices are related with the creativity components, namely in terms of technical knowledge and other competencies. For example, it was found a strong relationship between the components of creativity and the practices associated with rewards and benefits. Finally, according to the results the HRM practices emerge as potential enhancers and/or inhibitors of creativity in academic spin-offs. For example, some forms of recruitment, selection, rewards and training emerge as being related with creativity enhancers, while others emerge as being related with creativity inhibitors.